Difference Between Day and Night Temperatures Affects Stem Elongation in Tomato (Solanum lycopersicum) Seedlings via Regulation of Gibberellin and Auxin Synthesis - Ohtaka, Kinuka; Yoshida, Akiko; Kakei, Yusuke; Fukui, Kosuke; Kojima, Mikiko; Takebayashi, Yumiko; Yano, Kanako; Imanishi, Shunsuke; Sakakibara, Hitoshi (Frontiers in Plant Science, 2020)
Temperature is a critical environmental factor governing plant growth and development. The difference between day temperature (DT) and night temperature (NT), abbreviated as DIF, influences plant architecture. Subjecting plants to artificial DIF treatments is an effective strategy in ornamental horticulture. For example, negative DIF (when DT – NT < 0) generally inhibits stem elongation, resulting in dwarf plants. However, the mechanisms underlying stem growth regulation by DIF remains to be completely elucidated. In this study, we aimed to analyze the growth, transcriptome, and phytohormone profiles of tomato (Solanum lycopersicum) seedlings grown under different DIF treatments. Under positive DIF (when DT – NT > 0), in contrast to the control temperature (25°C/20°C, DT/NT), high temperature (30°C/25°C) increased stem length and thickness, as well as the number of xylem vessels. Conversely, compared with the positive high temperature DIF treatment (30°C/25°C), under negative DIF treatment (25°C/30°C) stem elongation was inhibited, but stem thickness and the number of xylem vessels were not affected. The negative DIF treatment decreased the expression of gibberellin (GA)-, auxin-, and cell wall-related genes in the epicotyl, as well as the concentrations of GAs and indole-3-acetic acid (IAA). The expression of these genes and concentrations of these hormones increased under high temperature compared to those under the control temperature positive DIF. Our results suggest that stem length in tomato seedlings is controlled by changes in GA and IAA biosynthesis in response to varying day and night temperatures.